Efficiency of constructed wetland systems cultivated with black oats treatment of domestic sewage - Eustáquio Júnior, Valdeir; Matos, Antonio Teixeira De; Monaco, Paola Alfonsa Vieira Lo; Campos, Lidiane Carvalho De; Borges, Alisson Carraro (Acta Scientiarum. Technology, 2011)
The objective of the present work was to evaluate the efficiency of a constructed wetland system cultivated with black oat (Avena strigosa Schreb) for the treatment of domestic sewage effluent from a septic tank, with emphasis on removal of carbonaceous matter, nutrients (N, P and K) and sodium. The experiment was conducted in four constructed wetland system (CWS) with horizontal subsurface flow for secondary/tertiary treatment domestic sewage. The CWS 1, 2, 3 and 4 received, respectively, organic load rates (OLR) of 100, 200, 400 and 600 kg ha-1 day-1 of BOD. Average efficiencies for removal of BOD, COD, total nitrogen, phosphorus, sodium and potassium were, respectively, 69.5, 70.2, 17.8, 26.2, 14.9 and 16.6%. Low efficiency in the removal of nutrients (N, P and K) was due a high OLR applied which provided also a large input of nutrients to the system. Sodium removal efficiency was low because it is a highly soluble ion and is poorly absorbed by plants. In general, lower OLR result in greater pollutant removals from the domestic sewage.

Com a realização deste trabalho, objetivou-se avaliar a eficiência do sistema alagado construído, cultivado com aveia preta forrageira (Avena strigosa Schreb), no tratamento de esgoto domestico, efluente de um tanque séptico, com ênfase na remoção de matéria carbonácea, nutrientes (N, P e K) e sódio. O experimento foi conduzido em quatro Sistemas Alagados Construídos (SACs) de escoamento subsuperficial horizontal para tratamento secundário/terciário de esgoto doméstico. Os SACs 1, 2, 3 e 4 receberam, respectivamente, taxas de carregamento orgânico (TCO) de 100; 200; 400 e 600 kg ha -1 dia -1 de DBO. A eficiência média na remoção de DBO, DQO, nitrogênio total, fósforo, sódio e potássio, foram, respectivamente, de 69,5; 70,2; 17,8; 26,2; 14,9 e 16,6%. A baixa eficiência na remoção de nutrientes (N, P e K) foi devida à alta TCO aplicada que proporcionou, também, grande aporte de nutrientes ao sistema. A eficiência de remoção de sódio foi baixa por ser um íon de grande solubilidade e devido à baixa absorção pelas plantas. No geral, menores TCOs proporcionaram maiores remoções de poluente do esgoto doméstico.
Keywords: Constructed wetlands; Wastewater; Pollution control